Situating Oneself in the Virtual: A Merleau-Pontian Approach to the Virtual Status of Corporeality - González-Araneda, Sergio (Tópicos, Revista de Filosofía, 2026)
This article discusses how the corporeality proposed in Merleau-Ponty’s phenomenology refers to an original virtual dimension. To this end, the relationship between movement and perception as constitutive of all lived bodes is reviewed. Subsequently, this relationship is problematized based on the Merleau-Pontian distinction between concrete movement and virtual movement. It is shown that movement not only permits the opening of fields of meaning, but fundamentally indicates a virtuality of these fields. Lastly, it is suggested to rethink the apriorism of the body, shifting it towards an apriorism of the virtual, insofar as the genesis of sensible being arises from a virtual dimension.